Probing Television and Media Education - Lazaro, Cecilia L. (Plaridel Journal of Communication, Media, and Society; Vol 4 No 2 (2007): New Media, 2007)
For 2007, the U.P. Gawad Plaridel award was given to Cecilia “Cheche” L. Lazaro for her outstanding contributions to the local television industry; her excellence and versatility in the field of television broadcasting as a broadcast journalist, producer, and media educator; and her production of critical and uncompromising programs that set the standards for Philippine broadcast journalism. As was the case with the past awardees, Lazaro read this paper during the U.P. Gawad Plaridel Paggawad at Lektyur on July 4, 2007 at the U.P. Film Institute Cine Adarna. More than 1,000 people attended the event, among them National Artist for Sculpture Napoleon V. Abueva; U.P. President Emerlinda R. Roman; U.P. Diliman Chancellor Sergio S. Cao; Former U.P. President Emanuel Soriano and wife Angelica A. Soriano; U.P. Board of Regent member Nelia T. Gonzalez; U.P. Faculty Regent Lourdes U. Barcenas; U.P. Vice President for Administration Arlene Samaniego; U.P. Vice President for Development Ruperto P. Alonzo; U.P. Vice President for Public Affairs Cristina P. Hidalgo; U.P. Assistant Vice President for Academic Affairs Florinda D.F. Mateo; U.P. Diliman Vice Chancellor for Student Affairs Elizabeth L. Enriquez; U.P. College of Music Dean Ramon Ma. G. Acoymo; U.P. Center for Women Studies Director Carol Sobritchea; 2006 U.P. Gawad Plaridel awardee Fidela Magpayo; Ayala Corporation Capital CEO Delfin L. Lazaro; ABS-CBN Head for News and Current Affairs Maria Ressa; ABS-CBN Head of News Gathering Group Charie Villa; Center for Media Freedom and Responsibility Deputy Director Luis V. Teodoro; Foundation for Worldwide People Power President Maria Lim-Ayuyao; Museo Pambata President and CEO Christina Lim-Yuson; Cultural Center of the Philippines President Nestor O. Jardin; Probe Foundation, Inc. Executive Director Yasmin Mapua-Tang; Ateneo de Manila University professor and television host Mercedes Fajardo-Robles; television hosts Bernadette Sembrano and Love Añover; artist Robert Alejandro; faculty members and mass communication students of U.P.; and officials, faculty members, and students of AMA Computer University, Assumption College, Ateneo de Manila University, Feati University, Miriam College, Philippine Women’s University, Polytechnic University of the Philippines, Quezon City Polytechnic University, St. Scholastica’s College, Trinity University of Asia, University of the East, and the University of Santo Tomas. The pre-show was anchored by 2007 Binibining Pilipinas Universe Ma. Anna Theresa L. Licaros while the main program was hosted by NBN’s Tinig ng Bayan hosts Mario Garcia and Marinela Aseron (who is also a faculty member of U.P. CMC’s Department of Broadcast Communication). The live program was directed by U.P. Film Institute assistant professor and television director Roehl L. Jamon.